A Three-Dimensional Model of Human Lysyl Oxidase, a Cross-Linking Enzyme - Vallet, Sylvain D. (ACS Omega, 2019)
[Image: see text] Lysyl oxidase (LOX) is a cross-linking enzyme identified 50 years ago, but its 3D structure is still unknown. We have thus built a 3D model of human LOX by homology modeling using the X-ray structure of human lysyl oxidase-like 2 as a template. This model is the first one to recapitulate all known biochemical features of LOX, namely, the coordination of the copper ion and the formation of the lysine tyrosylquinone cofactor and the disulfide bridges. Furthermore, this model is stable during a 1 μs molecular dynamics simulation. The catalytic site is located in a groove surrounded by two loops. The distance between these loops fluctuated during the simulations, which suggests that the groove forms a hinge with a variable opening, which is able to accommodate the various sizes of LOX substrates. This 3D model is a pre-requisite to perform docking experiments with LOX substrates and other partners to identify binding sites and to design new LOX inhibitors specific for therapeutic purpose.